2013
DOI: 10.5194/acp-13-9917-2013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transport model errors on the global and regional methane emissions estimated by inverse modelling

Abstract: Abstract.A modelling experiment has been conceived to assess the impact of transport model errors on methane emissions estimated in an atmospheric inversion system. Synthetic methane observations, obtained from 10 different model outputs from the international TransCom-CH 4 model inter-comparison exercise, are combined with a prior scenario of methane emissions and sinks, and integrated into the three-component PYVAR-LMDZ-SACS (PYthon VARiational-Laboratoire de Météorologie Dynamique model with Zooming capabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
93
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 79 publications
8
93
0
Order By: Relevance
“…Model errors in long-range transport, vertical convective transport, diffusion, and chemistry (e.g. Arellano Jr. et al, 2006;Fortems-Cheiney et al, 2011;Locatelli et al, 2013;Worden et al, 2013;Jiang et al, 2011Jiang et al, , 2013Jiang et al, , 2015 all adversely impact the inverse modeling of CO and other trace constituents (such as methane), and mitigating these errors in global models is challenging.…”
Section: Z Jiang Et Al: Regional Data Assimilation Of Multi-spectramentioning
confidence: 99%
“…Model errors in long-range transport, vertical convective transport, diffusion, and chemistry (e.g. Arellano Jr. et al, 2006;Fortems-Cheiney et al, 2011;Locatelli et al, 2013;Worden et al, 2013;Jiang et al, 2011Jiang et al, , 2013Jiang et al, , 2015 all adversely impact the inverse modeling of CO and other trace constituents (such as methane), and mitigating these errors in global models is challenging.…”
Section: Z Jiang Et Al: Regional Data Assimilation Of Multi-spectramentioning
confidence: 99%
“…Systematic errors in CTMs also have significant impacts on inverse estimates. In Locatelli et al (2013), it was shown that transport model errors are responsible for an uncertainty of 27 Tg CH 4 year −1 in the estimations of methane fluxes by inverse modeling at the global scale. Moreover, Locatelli et al (2015) showed that stratosphere-troposphere exchanges are systematically too fast in the version of LMDz (Laboratoire de Météorolo-gie Dynamique model with Zooming capability) using a low vertical resolution (19 levels), which could largely impact the estimation of gas fluxes, like N 2 O, whose stratospheric mixing ratios influence tropospheric mixing ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Locatelli et al (2015) showed that stratosphere-troposphere exchanges are systematically too fast in the version of LMDz (Laboratoire de Météorolo-gie Dynamique model with Zooming capability) using a low vertical resolution (19 levels), which could largely impact the estimation of gas fluxes, like N 2 O, whose stratospheric mixing ratios influence tropospheric mixing ratios. Furthermore, following Patra et al (2011), Locatelli et al (2013) showed that a bad representation of the interhemispheric exchange in an ensemble of state-of-the-art CTMs can explain most of the discrepancies in the global methane fluxes derived by inverse modeling using these different CTMs.…”
Section: Introductionmentioning
confidence: 99%
“…The model-data mismatch may be compared between an inversion that uses the "true" transport to calculate the sensitivity matrix versus that of an inversion that uses a different transport model (e.g., Chevallier et al, 2010;Houweling et al, 2010;Berchet et al, 2015;Locatelli et al, 2013). Assuming that the difference in performance between these two transport models is comparable to the difference between transport models used in real-data inversions, the inversion with inconsistent transport can be compared to the inversion with consistent transport to determine how much the inconsistencies in transport affect the inversion.…”
Section: Synthetic Data Experimentsmentioning
confidence: 99%
“…Posterior flux errors and error covariances can be used to assess the impact of modeling simplifications or data limitations on the accuracy and precision of flux estimation (e.g., Berchet et al, 2015;Gourdji et al, 2010). OSSEs can also be used to understand sources of bias through a simple differencing of posterior and "true" fluxes (e.g., Locatelli et al, 2013;Thompson et al, 2011;Basu et al, 2016;Bloom et al, 2016). Similar tests can be run to determine the effects of observational biases and mistuning of error statistics on the accuracy of posterior estimates (e.g., Baker et al, 2010).…”
Section: Synthetic Data Experimentsmentioning
confidence: 99%